Why Hydrological Maze: The Hydropedological Trigger? Review of Experiments at Chuzhou Hydrology Laboratory - Gu, W.Z. (2020)
he objective of this study was to reveal the hydrological maze through a comprehensive review of decades of work since the 1980s on observations and experiments using a combination of natural and artificial catchments at the Chuzhou Hydrology Laboratory in China, highlighting the role of hydropedology in hillslope and catchment hydrology based on long‐term monitoring of surface and subsurface flows at various soil depths and at different spatial scales. A conception has emerged that indicates the fundamental control of hydropedological factors (such as soil types, soil properties, and their spatial variations) as the trigger for the hydrological maze, including runoff generation, runoff composition, flow heterogeneity, and various hydrological puzzles. It is clear that the vadose zone is the key source for nonlinear and dissipative complexity in the hydrological maze that is intertwined with hydrochemical and hydroecological dynamics. Therein lies the hope for new hydrological insights and possible solutions to the hydrological maze.